First integrals for problems of calculus of variations on locally convex spaces - Rocha, E.A.M. (2011)
The fundamental problem of calculus of variations is considered when solutions are differentiable curves on locally convex spaces. Such problems admit an extension of the Eulcr-Lagrange equations (Orlov. 2002) for continuously normally differentiable Lagrangians. Here, we formulate a Legcndre condition and an extension of the classical theorem of Emmy Noethcr, thus obtaining first integrals for problems of the calculus of variations on locally convex spaces. © Balkan Society of Geometers, Geometry Balkan Press 2008.